PENINGKATAN VO₂MAX MAHASISWA CABANG OLAHRAGA TINJU MELALUI KOMBINASI LATIHAN DOUBLE SKIPPING DAN BOX JUMP - Duhe, Edy Dharma Putra; Haryani, Meri; Irawan, Safri; Nurkhoiroh; Haryanto, Arief Ibnu; Suardika, I Kadek; Mamonto, Nurwitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the increase in VO₂Max in boxing students through a combination of double skipping and box jump training. The study used a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The study subjects were 15 boxing students specializing in the Sports Coaching Education Study Program, consisting of 9 males and 6 females, aged 18–22. Treatment consisted of a combination of double skipping and box jump training for 6 weeks, performed 3 times per week. VO₂Max was measured using the Multistage Fitness Test/Bleep Test before and after treatment. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Wilcoxon signed-rank test, percentage increase, and effect size. The results showed an average increase in VO₂Max from 36.47 to 39.60 mL/kg/min, representing an increase of 3.13 mL/kg/min, or 8.61%. The Wilcoxon test showed a significant difference with p < 0.001 and an effect size of 0.88. Thus, the combination of double skipping and box jump training effectively increased boxing students' VO₂Max.